Copper-Catalyzed Skeletal Rearrangement of O-Propargylic Aryloximes into Four-Membered Cyclic Nitrones – Chirality Transfer and Mechanistic Insight - Nakamura, Itaru; Kudo, Yu; Araki, Toshiharu; Zhang, Dong; Kwon, Eunsang; Terada, Masahiro (Synthesis, 2012)
Copper-catalyzed skeletal rearrangement of O-propargylic aryloximes (E)-1 were carried out to afford the corresponding four-membered cyclic nitrones 2 in good to excellent yields. The optimal reactions conditions of the highly regioselective reactions involved the use of [CuCl(cod)]2 in acetonitrile at 70 °C. In the case of (Z)-1, however, the reaction proceeded in the absence of the copper catalysts to afford the identical compound 2 in good yields. Furthermore, the reactions were also carried out using chiral substrates (R)-1 in the presence of Cu catalysts to afford (R)-2 with good levels of chirality transfer.
Keywords: copper; skeletal rearrangement; oxime; nitrone; chirality transfer